Risk, risk conflicts, sub-politics and social and environmental accounting and accountability in Scottish salmon farming - Georgios Georgakopoulos (SPOUDAI - Journal of Economics and Business, 2018)
The aim of this paper is to offer a theoretical analysis, inspired by research into social theories of risk, of the social and environmental accounting processes observed in an earlier empirical study on Scottish salmon farming. Social and environmental accounting and accountability processes in Scottish salmon farming appeared to be similar to those described within the Risk Society thesis. Demands for social and environmental accounts within this risk arena could be seen to relate to different perceptions of the risks associated with salmon farming. There was conflict over both the meaning of risks and the methodology of measuring and communicating them. Social and environmental accounts were part of this contest for control of governing these risks. Insights from the Risk Society thesis offer useful understandings into appreciating Social and Environmental Accounting (SEA); in particular the role of sub-political movements and the role of sub-political accounting. The importance of recognizing social and environmental accounting as part of a wider reflexive process is also an important implication of this paper.
Keywords: M14; M41; M48; 330; Social and Environmental Accounting; Risk; Reflexivity; sub-political accounting; Salmon Farming